2019
DOI: 10.3389/fphar.2019.01495
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine Induced Parkinsonism in Migraine Group: A Nationwide Population-Based Study

Abstract: Background: Flunarizine (Fz) is a first-line prophylactic medication that is widely used in migraine. However, Fz has been recognized as a potential cause of drug-induced parkinsonism for a long time. However, to our knowledge, there has been no population-based subgroup analyses for Fz-induced parkinsonism (FIP) in migraine patients. Methods: Data were obtained from the Taiwan's National Health Insurance Research Database. The study comprised 6,470 migraine patients who were divided into two groups, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The prevention of migraines is not to prevent the illness but to reduce the frequency of migraine attacks (9). The traditional preventive medications on migraines frequently lead to an early suspension of treatment due to their poor efficacy and tolerability in migraine people (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of migraines is not to prevent the illness but to reduce the frequency of migraine attacks (9). The traditional preventive medications on migraines frequently lead to an early suspension of treatment due to their poor efficacy and tolerability in migraine people (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [128] showed that the odds ratio of the risk of developing PKN in FNZ users when compared to non-FNZ users is 4.95 (2.71-9.03). In another study, Lin et al [129] revealed that a longer duration of exposure to FNZ and high FNZ doses are significantly associated with the occurrence of PKN.…”
Section: Incidencementioning
confidence: 96%
“…The majority of the incidences of abnormal movements associated with CNZ/FNZ were not well described in the literature. Table 3 is a resume of the percentages of MD secondary to CNZ/FNZ; the data was extracted from clinical trials and other populationbased studies [26,34,48,49,55,70,76,77,97,115,119,123,127,129]. The incidences of CNZ/FNZ-induced abnormal movements, in general, vary throughout the literature, but the range is much smaller than other drugs with postmarketing evaluation such as valproic acid [132]; for example, extrapyramidal symptoms were found with the use of CNZ/FNZ in Verspeelt and colleagues in 4.30% of individuals with migraine individuals, but in the vestibular vertigo subgroup it was 0.91% [77].…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, more than 16% of the global population is affected by the attacks of migraine [2]. Unfortunately, since many drugs are available for the therapy of migraine, such as NSAIDS, triptans, ergots, they all have some contraindications or severe adverse effects in certain aspects [3]. Therefore, further studies are needed on the treatment of the migraine, which ultimately may help patients suffering from it by improving the adverse effects.…”
Section: Introductionmentioning
confidence: 99%